Development and evaluation of new coupling system for lower limb prostheses with acoustic alarm system - Eshraghi, Arezoo; Abu Osman, Noor Azuan; Gholizadeh, Hossein; Ahmadian, Jalil; Rahmati, Bizhan; Wan Abas, Wan Abu Bakar (Nature Research, 2013)
Individuals with lower limb amputation need a secure suspension system for their prosthetic devices. A new coupling system was developed that is capable of suspending the prosthesis. The system's safety is ensured through an acoustic alarm system. This article explains how the system works and provides an in vivo evaluation of the device with regard to pistoning during walking. The system was designed to be used with silicone liners and is based on the requirements of prosthetic suspension systems. Mechanical testing was performed using a universal testing machine. The pistoning during walking was measured using a motion analysis system. The new coupling device produced significantly less pistoning compared to a common suspension system (pin/lock). The safety alarm system would buzz if the suspension was going to fail. The new coupling system could securely suspend the prostheses in transtibial amputees and produced less vertical movement than the pin/lock system.